The impact of callanetics exercises on some biomotor skills and physical characteristics of women with osteoporosis aged 45–55 years - Khalil, Lamyaa Abdul Sattar (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The purpose of this study was to demonstrate the value of callanetics exercises in enhancing some aspects of the health fitness of women with osteoporosis and to determine how callanetics exercises affect elderly women with osteoporosis in terms of enhancing certain aspects of health fitness. The sample included women with osteoporosis of the Department of Physiotherapy at Baghdad Hospital, aged 45–55 years, during the period from 1/3/2022 to 9/8/2022. The callanetics exercises applied produced a decrease in the percentage of fat, with a decline in the values of hip and thigh circumferences.